PELAYANAN KESEHATAN PASIEN DI PUSKESMAS BINTARA MENGGUNAKAN METODE WAITING LINE - Tinawati Pasaribu (Cakrawala - Jurnal Humaniora, 2012)
The importance of health for all people, children, parents and young people are no exception rich and poor. Health can not be bought, but can we keep health by regulating a healthy lifestyle. The rapid era of increasingly sophisticated medical technology, but also more expensive health costs. Many people who can not afford could not go in because of the high cost of hospital and medical therefore the government to build health center in each village or district. Health Center is a community health development center that also foster community participation as well as provide a comprehensive and integrated healthcare to communities in the region in the form of his main activities. Unfortunately, the facilities provided by the health center doctor yet standard example. Health Center only two / three doctors to serve patients so much. At the Bintara health center alone there are approximately 3 doctors to serve approximately 100 people / day and make buildup patients, the authors analyzed here buildup patients using the waiting line. Waiting Line Method is very useful to analyze the queue length, average service time, average waiting time. With the help of Waiting Line calculation method will yield information about the intensity level of service in the queue that can be taken into consideration for the development and planning of a service quality improvement and service companies. Keywords: Health Services, Patient, Health Center, Waiting Line